THE INFLUENCE OF CORPORATE SOCIAL RESPONCIBILITY (CSR) IN THE SOCIAL, ECONOMIC AND ENVIRONMENTAL FIELDS ON PAWNSHOP CUSTOMER LOYALTY IN PALEMBANG CITY - Warni, Zubaidah; Octarinie, Nenny; Gunarti, Triana Sri; Pangestu, Fauzi Dwi (TECHNOBIZ : International Journal of Business, 2024)
This study uses a quantitative approach with a sample size of 40 people determined using the Accidental Sampling technique.  The results of multiple regression testing show that all independent variables (CSR in the social field, CSR in the economic field and CSR in the environmental field) have a positive effect on pawnshop customer loyalty and in Palembang City. The biggest positive influence on pawnshop customer loyalty is on the economic CSR variable, this is shown from the regression coefficient value of 0.274, then followed by the social CSR variable which is shown from the regression coefficient value of 0.181 and CSR in the environmental field of 0.173. Based on the coefficient of determination test, it is known that the R2 (R Square) number is 0.123 or (12.3%).  This shows that the percentage contribution of CSR in the social field, CSR in the economic field and CSR in the environmental field to customer loyalty.